2016
DOI: 10.1016/j.concog.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias to pain-relevant body locations: New methods, new challenges

Abstract: In a recent issue of Consciousness and Cognition, Filbrich, Torta, Vanderclausen, Azanon, and Legrain (2016) commented on a paper in which we used a tactile Temporal Order Judgment (TOJ) task to show that expecting pain on a specific body location biased attention to that location (Vanden Bulcke, Crombez, Durnez, & Van Damme, 2015). Their main criticism is that the effects are likely to reflect response bias rather than genuine attentional bias. We agree that the TOJ task used may be susceptible to response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…For example, a number of studies have shown that participants threatened with pain on one hand perceived innocuous tactile stimuli at that hand earlier than tactile stimuli on the other hand 39,41 . These findings have been suggested to reflect an "attentional bias" towards body locations where pain is expected 36 . However, the behavioral indicators used in these studies are not entirely free from alternative explanations such as response strategies, because the stimuli to which responses were measured were task-relevant, making it difficult to infer genuine attentional effects 13 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, a number of studies have shown that participants threatened with pain on one hand perceived innocuous tactile stimuli at that hand earlier than tactile stimuli on the other hand 39,41 . These findings have been suggested to reflect an "attentional bias" towards body locations where pain is expected 36 . However, the behavioral indicators used in these studies are not entirely free from alternative explanations such as response strategies, because the stimuli to which responses were measured were task-relevant, making it difficult to infer genuine attentional effects 13 .…”
Section: Introductionmentioning
confidence: 91%
“…There is some behavioral evidence, though, that experimentally induced anticipation of pain results in enhanced processing of somatosensory input at to the body location where pain is expected, indicating heightened attending to that location 9,36 . For example, a number of studies have shown that participants threatened with pain on one hand perceived innocuous tactile stimuli at that hand earlier than tactile stimuli on the other hand 39,41 .…”
Section: Introductionmentioning
confidence: 99%
“…These results speak against a protective inhibition mechanism and instead point towards the self-focus hypothesis. Specifically, this account argues that pain shifts attention inwards [15,59,60] and that such a self-oriented focus hampers motor simulation [10,34,54]. Furthermore, because the results of Experiments 1 and 2 could not be distinguished, this suggests that the self-focus account can also explain the results of Experiment 1, where pain was coupled to movement execution.…”
Section: Interim Discussionmentioning
confidence: 96%
“…According to the protective inhibition account, imitative responses that lead to pain are inhibited [44,45]. In contrast, according to the self-focus account, pain shifts attention to the self [15,59,60], and this self-oriented focus then interferes with automatic imitation [10,34,54]. Crucially, the protective inhibition account predicts that automatic imitation should be selectively reduced when observing movements associated with pain, whereas the self-focus account instead predicts that automatic imitation should be reduced regardless of the observed movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation